Orientation Regulation of Phenylethylammonium Cation Based 2D Perovskite Solar Cell with Efficiency Higher Than 11%. Issue 14 (30th January 2018) - Zhang, Xinqian; Wu, Gang; Fu, Weifei; Qin, Minchao; Yang, Weitao; Yan, Jielin; Zhang, Zhongqiang; Lu, Xinhui; Chen, Hongzheng
Abstract: Increasing the power conversion efficiency (PCE) of the two‐dimensional (2D) perovskite‐based solar cells (PVSCs) is really a challenge. Vertical orientation of the 2D perovskite film is an efficient strategy to elevate the PCE. In this work, vertically orientated highly crystalline 2D (PEA)2 (MA)n–1 Pbn I3n+1 (PEA= phenylethylammonium, MA = methylammonium, n = 3, 4, 5) films are fabricated with the assistance of an ammonium thiocyanate (NH4 SCN) additive by a one‐step spin‐coating method. Planar‐structured PVSCs with the device structure of indium tin oxide (ITO)/poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate)/(PEA)2 (MA)n–1 Pbn I3n+1 /[6, 6]‐phenyl‐C61‐butyric acid methyl ester/bahocuproine/Ag are fabricated. The PCE of the PVSCs is boosted from the original 0.56% (without NH4 SCN) to 11.01% with the optimized NH4 SCN addition at n = 5, which is among the highest PCE values for the low‐ n ( n < 10) 2D perovskite‐based PVSCs. The improved performance is attributed to the vertically orientated highly crystalline 2D perovskite thin films as well as the balanced electron/hole transportation. The humidity stability of this oriented 2D perovskite thin film is also confirmed by the almost unchanged X‐ray diffraction patterns after 28 d exposed to the moisture in a humidity‐controlled cabinet ( H r = 55 ± 5%). The unsealed device retains 78.5% of its original PCE after 160 h storage in air atmosphere with humidity of 55 ± 5%. The results provide an effective approach toward a highly efficient and stable PVSC for future commercialization. Abstract : The advantage of phenylethylammonium (PEA + ) in forming pinhole‐free 2D (PEA)2 (methylammonium (MA)) n −1 Pb n I3 n +1 n = 3, 4, 5) perovskite film with vertical orientation and high crystallinity under assistance of an ammonium thiocyanate additive by one‐step spin‐coating method is demonstrated. The optimized planar‐structured perovskite solar cell based on vertically oriented (PEA)2 (MA)4 Pb5 I16 ( n = 5) film presents the best power conversion efficiency of 11.01% with excellent stability.